2007
DOI: 10.1080/13880200701574992
|View full text |Cite
|
Sign up to set email alerts
|

Anin Vitro. Comparative Study on the Antioxidant Activity and Determination of Antibacterial Potential of Atorvastatin and Simvastatin

Abstract: Free radicals generated from oxidative stress (OS) have been depicted in the causation of cancerous and noncancerous diseases in humans. Increase in fat content of the body may favor the deleterious effect of free radical attack. The generation of free radicals is enhanced in respiratory burst during bacterial infection. The level of plasma membrane cholesterol appears to be critical in the regulation of microbial entry, intracellular trafficking, and exit. The current study was designed to compare the in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The ferric reducing anti‐oxidant power (FRAP) assay was performed by incubating ferric ion with TPTZ in the presence and absence of rosuvastatin (0.01–1 mg/mL) in a total volume of 1 mL 17 . After incubation, the OD of the reaction mixture was measured at 540 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The ferric reducing anti‐oxidant power (FRAP) assay was performed by incubating ferric ion with TPTZ in the presence and absence of rosuvastatin (0.01–1 mg/mL) in a total volume of 1 mL 17 . After incubation, the OD of the reaction mixture was measured at 540 nm.…”
Section: Methodsmentioning
confidence: 99%
“…3,4 Studies of the statins showed that they delay the progression of coronary artery disease, 5 reduce mortality from cardiovascular diseases 6 and have anti-inflammatory 7 and anti-oxidant activity. 8 There are some reports on testing HMG-CoA reductase inhibitors against cancer, 9 Alzheimer's disease, and osteoporosis. 10 a Quantum Chemistry Group, Faculty of Chemistry, A. Mickiewicz University, Grunwaldzka 6,Poznan,Poland b BioInfoBank Institute, Limanowskiego 24A, 60-744, Poznan, Poland.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the application of CoQ10 in CVD, its use against the adverse effect of drugs, mainly statins, in the intervention of CVD has recently attracted attention. Nevertheless, the antioxidant property of statins [32,33] can block the endogenous biosynthesis of CoQ10 required for the ETC, resulting in cardiomyopathy and muscle pain [34] . CoQ10 supplementation (100 mg/d) for 30 d has been found to decrease the muscle pain associated with statin treatment [35] .…”
Section: Of Mitochondria In the Cardiomyocytesmentioning
confidence: 99%